The Extent of the Effect of the Use of Virtual Reality Technology on some Physiological Variables for Players Running Long Distances - Thneibat بكر (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This study aimed to identify the impact of the use of virtual reality (VR) technology on some physiological variables, and the study aimed to find-out the statistical differences of the impact of the use of virtual reality technology on the variables under study The population of the study consists of (20) players (long distance running). and the sample of the study included (9) players from the players (running long distances) in Sports Activity Center at Mutah University. The researcher used the quasi-experimental approach with its scientific steps and procedures due to its suitability with the nature of this study. The results of the study showed that VR, using three-dimensional glasses, has a clear effect on the two study variables (Heart rate (HR) and (Rated Perceived Exertion (RPE)) on various stress levels (60 watts, 90 watts, 120 watts), and150 watts), where the results of the study showed that VR has a statistically significant effect of 120 watts on the heart rate (HR) variable. The results of the study also showed that VRity has a statistically significant effect (150W) on the variable of (RPE). The study recommended that physical laboratories should contain specialized rooms equipped with VR, and it recommended that studies should be run on VR in relation to physiological variables such as Actic, Glucose, Endrophins and Dopamine).